KESESUAIAN KAWASAN UNTUK PENGEMBANGAN EKOWISATA HUTAN MANGROVE KUALA LANGSA - Kurnia Tari; Iswahyudi Iswahyudi; Dolly S Siregar (Jurnal Belantara, 2020)
Langsa City is mostly in the form of land and coastal areas, especially the Kuala Langsa area which has the potential to be developed into an ecotourism development area because the mangrove ecosystem is still natural and preserved. This study aims to determine the level of land suitability for the development of mangrove forest ecotourism in Kuala Langsa. Primary data in the form of mangrove density, mangrove thickness, types of mangroves, tides, and biota objects were obtained through observation at 6 observation locations using Purposive sampling and Line transect point methods, while secondary data included geographical conditions, and tidal data obtained through literature studies. Vegetation data were analyzed by calculating plant species density and tourism suitability analyzed using tourism suitability index (IKW). Mangrove species found at the study site included, Bruguiera gymnorrhiza, Ceriops tagal, Rhizophora apiculata, Rhizophora mucronata, Sonneratia caseolaris and Xylocarpus granatum. The results showed that the IKW value of 60% included in the S2 category (as appropriate). The limiting factor is the density of mangroves which only have a value of 8 with the S3 conformity category (as conditional). With the limiting factor is the density of mangroves which only have a value of 4 with the suitability category S3 (not suitable). As for suggestions that can be given to the manager of Kuala Langsa mangrove forest Ecotourism so that the existence of Ecotourism can be sustainable is the need for Pentahelix Synergy in the management of the ecotourism.